C-reactive protein, as a marker for predicting acute appendicitis and its severity in KVG medical college and hospital, Sullia - Ramu, Abhirup H.; Kenchetty, Priyanka; Chidananda, Aishwarya K. (International Surgery Journal, 2021)
Background: Appendicectomy for suspected acute appendicitis is a common procedure. The rate of normal appendices unnecessarily removed remains high despite several techniques and investigations used to improve the diagnostic accuracy. This study emphasizes the value of C reactive protein (CRP) in three groups of patients operated for clinical suspicion of acute appendicitis with different finding at appendicectomy namely an un-inflamed appendix, uncomplicated acute appendicitis or complicated acute appendicitis. Methods: This prospective study was performed on 100 consecutive patients who were operated on for treatment of acute appendicitis in KVG medical college and hospital between 01 August 2019 to 01 February 2021. Clinically proven by a surgeon, patients underwent appendicectomy. Serum CRP results of all patients were determined. Sensitivity, specificity, positive predictive value and negative predictive value were calculated. Statistical analysis will be made using descriptive statistic and SPSS version 21 was used for analysis. Results: The percentage of negative laparotomies was 13% and surgeon ‘s clinical suspicion was true in 87%. Preoperative CRP values were false negative in 21 patients with appendicitis and false positive in 2 patients with normal appendix. The difference of true and false results between CRP tests and surgeon’s diagnosis was statistically significant (p=0.001). Present study revealed, sensitivity=76%, specificity=87.5%, positive predictive value=96% and negative predictive value=41%. Conclusions: Serum C reactive protein when elevated supports the surgeon’s clinical diagnosis of acute appendicitis. It can be used frequently to diagnosis the acute appendicitis, so that the complication rate and negative laparotomies can be avoided.